Impact of microwave heated food on health - Ghazaly, Nawal Ahmed El; Radwan, Eman Hashem; Gawad, Horeya Said Abd El; Kamel, Karolin; Barakat, Amel (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Microwave has attracted a great deal of attention due to its increase usage in occupational environment, which leads to a large number of publications regarding health hazards of microwave. The aim of this research was to investigate the biological effects of microwave heated food on the blood and organs of the experimental mice.The present study had one goal is to evaluate the effects of Â feeding on microwave heated food. These evaluations were done on male Swiss albino mice (pre (one month) and post (three months)-pubertal ages). All the results of albumin and bilirubin showed that an elevation in the levels of two parameters while, the protein concentration was decreased. The results showed decline in glutathione peroxidase and superoxide dismutase as well as increase in malondahyde concentrations according to the oxidative stress which leads to physiological disturbances. The results of the present study suggests that the microwave radiation has adverse effects on liver functions leading to histological and physiological impairment.